Patching bits won't fix vocational education in Australia – a new model is needed. (1st September 2016) - Wheelahan, Leesa
Abstract: Australia's vocational education and training (VET) qualifications comprise units of competency that are bundled together in qualifications and nestled in training packages developed for particular industries. This article argues that this model is broken and cannot be fixed by patching bits of the system. Competency-based training (CBT) is based on an atomistic ontology that results in the fragmentation of knowledge and the atomisation of skill. CBT underpins a fragmented VET system with thousands of qualifications. It facilitates a market that has resulted in: thousands of private providers; the erosion of technical and further education (TAFE) institutions as the public provider; the transfer of unprecedented amounts of public funding to private profits; and, scandals and rorts. The same atomistic ontology underpins VET qualifications, the VET system and the VET market. The article concludes by briefly discussing an alternative model of qualifications using the capabilities approach.